Exoteric modernisms : Progressive Era realism and the aesthetics of everyday life - Collins, Michael J. (Michael James), 1984- (Modern American literature and the new twentieth century., 2023)
Applies new understandings of realism as a political aesthetic to Progressive Era Literature, arguing for its radicalism politically and culturally. This book is an account of how American realism in the Progressive Era contributed to debates about modernity. It uses the anthropological theories of Franz Boas, and Jacques Ranciere's work on aesthetics and politics to develop a mode of reading class and culture that challenges conventional interpretations that pit the two modes of representation in opposition. It paints a picture of the late-nineteenth century, prior to modernism, as an aesthetically exciting, original, and politically radical stage in American life to reinvigorate realism as a radical aesthetic practice, with implications for understandings of American literature both in the past and into the future.--